1998
DOI: 10.1111/j.1349-7006.1998.tb00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Glandular Stomach Cancers in Helicobacter pylori‐sensitive Mongolian Gerbils Treated with N‐Methyl‐N‐nitrosourea and N‐Methyl‐N′‐nitro‐N‐nitrosoguanidine in Drinking Water

Abstract: An animal model of stomach carcinogenesis was established using Mongolian gerbils with Nmethyl-N-nitrosourea (MNU) and N-methyl-N′ ′ ′ ′-nitro-N-nitrosoguanidine (MNNG) as the carcinogens. In addition, the sensitivity of these gerbils to Helicobacter pylori (H. pylori) was confirmed. One hundred and sixty specific pathogen-free male MGS/Sea animals, 7 weeks old, were treated with MNU in the drinking water (30 ppm for alternate weeks to give 10 weeks exposure, or 10 ppm or 3 ppm for 20 weeks continuous exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 21 publications
(22 reference statements)
1
80
0
Order By: Relevance
“…The incidence of adenocarcinomas was significantly higher in the early (H. pylori+MNU) group A than the early MNU-alone group D. In the MNU-alone groups, adenocarcinomas were detected only in early exposed gerbils, indicating that MNU-induced chemical gastric carcinogenesis depends not only on the concentration, 5) but also on the timing of administration in this model. Nonetheless, there was no significant difference in the incidences of gastric cancers among the MNU-alone groups D, E, and F. Thus, the early H. pylori infection was considered as a strong promoter for gastric carcinogenesis, even though administration of MNU at an early age also possibly contributed to the high incidence of adenocarcinomas in group A.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The incidence of adenocarcinomas was significantly higher in the early (H. pylori+MNU) group A than the early MNU-alone group D. In the MNU-alone groups, adenocarcinomas were detected only in early exposed gerbils, indicating that MNU-induced chemical gastric carcinogenesis depends not only on the concentration, 5) but also on the timing of administration in this model. Nonetheless, there was no significant difference in the incidences of gastric cancers among the MNU-alone groups D, E, and F. Thus, the early H. pylori infection was considered as a strong promoter for gastric carcinogenesis, even though administration of MNU at an early age also possibly contributed to the high incidence of adenocarcinomas in group A.…”
Section: Discussionmentioning
confidence: 86%
“…3,4) Our previous studies have proven that N-methyl-N-nitrosourea (MNU) and Nmethyl-N′-nitro-N-nitrosoguanidine (MNNG) can induce glandular stomach cancers in Mongolian gerbils (MGs), and further demonstrated promoting effects due to H. pylori infection on tumor development. [5][6][7] Since there has been no experimental investigation to determine the significance of H. pylori infection in children in relation to the risk of development of gastric cancer in adult life, we here examined the effects of H. pylori infection acquisition time on incidence of adenocarcinomas, serum anti-H. pylori IgG antibodies and gastrin levels in MGs.…”
Section: Abstract: Helicobacter Pylori -Gastric Carcinogenesis -Mongmentioning
confidence: 99%
“…Sections of 3 mm thickness were prepared and stained with hematoxylin and eosin. Neoplastic lesions in the stomach were diagnosed as previously described (36). The size of a gastric cancer was determined as the maximum diameter of the gastric cancer in the neighboring sections.…”
Section: Histological Analysismentioning
confidence: 99%
“…More recently, Tatematsu et al 9 have established a Mongolian gerbil model in which gastric carcinogenesis is induced by N-methyl-N-nitorosourea (MNU), and Sugiyama et al 10 have demonstrated that H. pylori has both co-initiating and promoting effects on MNU-induced gastric carcinogenesis in this model. However, the evolution of the histopathological changes taking place in the gastric mucosa of experimentally infected Mongolian gerbils has not been described in a systematic fashion.…”
mentioning
confidence: 99%